Ancient DNA from bulk bone reveals past genetic diversity of vertebrate fauna on Kangaroo Island, Australia. (15th June 2021) - Seersholm, Frederik V.; Grealy, Alicia; McDowell, Matthew C.; Cole, Theresa L.; Arnold, Lee J.; Prideaux, Gavin J.; Bunce, Michael
Abstract: It is indisputable that much of Australia's modern biodiversity decline was triggered by European settlement. However, the driver(s) of pre-European extinctions and extirpations are more challenging to identify, particularly on islands where animals are faced with the additional pressures imposed by isolation. Kangaroo Island, South Australia, has been identified as a potential haven for the reintroduction of endangered animals, but the genetic relationship between reintroduction candidates on the mainland and their extinct relatives on Kangaroo Island is poorly understood. Here, we present a late Pleistocene to mid-Holocene genetic record from Kangaroo Island based on bulk bone metabarcoding of two thousand bone fragments excavated from Kelly Hill Cave. We detect 33 species of bird, reptile, fish and mammal and report additional intra-specific genetic diversity in Kangaroo Island's now extinct population of spotted-tailed quoll. Furthermore, we provide genetic evidence that the Eastern grey kangaroo formerly inhabited Kangaroo Island. Taken together, these data establish a more complete baseline of local biodiversity against which reintroduction programmes and bushfire recovery measures can be evaluated, which is more important than ever in light of the recent fires that devastated much of Kangaroo Island's flora and fauna. Highlights: A genetic biodiversity baseline for Kangaroo Island before European arrival. Genetic identification of 33 species of bird, reptile, fish and mammal. New haplotypes from the extinct Kangaroo Island population of spotted-tailed quoll. Genetic evidence that the Eastern grey kangaroo once inhabited Kangaroo Island.